2014
DOI: 10.11144/javeriana.sc19-3.hpnm
|View full text |Cite
|
Sign up to set email alerts
|

Hepáticas del Parque Natural Municipal “Robledales de Tipacoque”, Boyacá-Colombia

Abstract: In high mountain ecosystems, Hepaticae is prominent and are essential to regulate and maintain hydrological cycles; they also contribute to nutrient recycling. We sampled five different substrates (decomposing matter, tree base, bare soil, rocks and flush root) of the "Robledales de Tipacoque" Natural Park and recorded 52 species of Hepaticae belonging to 21 genera and 12 families. The families having the highest number of species were the Plagiochilaceae with 22 (40.7%) and Lejeuneaceae with nine (16.6%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The indicator species analysis showed that Clasmatocolea vermicularis, Fissidens serratus, Lophocolea bidentata, Monoclea gottschei, Noteroclada confluens, Symphyogyna brongniartii, Symphyogyna brasiliensis, Plagiochila laetevirens, and Rhodobryum huillense were the best indicators of the control zone, related to uncontaminated water. Accordingly, Lophocolea bidentata, Symphyogyna brongniartii, and Monoclea gottschei occur more abundantly in shady habitats with vegetation of undisturbed forests, due to the fact that they are sensitive to environmental changes [59,60]. Conversely, Fissidens elegans, Riccia crassifrons, and Marchantia polymorpha were the best indicators of more urbanized zones such as in southern, central, and northern areas with greater impact of anthropogenic disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The indicator species analysis showed that Clasmatocolea vermicularis, Fissidens serratus, Lophocolea bidentata, Monoclea gottschei, Noteroclada confluens, Symphyogyna brongniartii, Symphyogyna brasiliensis, Plagiochila laetevirens, and Rhodobryum huillense were the best indicators of the control zone, related to uncontaminated water. Accordingly, Lophocolea bidentata, Symphyogyna brongniartii, and Monoclea gottschei occur more abundantly in shady habitats with vegetation of undisturbed forests, due to the fact that they are sensitive to environmental changes [59,60]. Conversely, Fissidens elegans, Riccia crassifrons, and Marchantia polymorpha were the best indicators of more urbanized zones such as in southern, central, and northern areas with greater impact of anthropogenic disturbances.…”
Section: Discussionmentioning
confidence: 99%